HUBUNGAN PREDISPOSSING FACTORS DENGAN PERILAKU MEROKOK PADA REMAJA DI KELURAHAN KETINTANG KOTA SURABAYA - Novi Triyas Diyanto; Dya Sustrami; Sukma Ayu C Kirana (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Background: Smoking is a habit is detrimental to health. Cigarettes are known to contain many poisons ad harmful chemicals that can cause various diseases such as heart disease, stroke and cancer. At present Indonesia is still the third country with the most active smokers in the world. This atudy aims to determine smoking behavior in adolescent in Ketintang Village, Surabaya City. Method: This type of research is quantitative, with a cross sectional approach. The total population is 206 respondents. The sample was taken by accidental sampling. This instrument uses a questionnaire. The Data was analysed by using chi square statistical test with significance level ? ? 0.05. Results: The results showed predisposed factors knowledge (? = 0,019), behavior (? = 0,000), and perception (? = 0.000). Conclusion: The implication of this study is that the society and parents are expected to guide and pay more attention to adolescent relationships. provide information about the dangers of smoking for himself and those around him.